Klestadt's cyst - Kamal, Reet (Medknow Publications & Media Pvt Ltd, 2011)
The nasolabial cyst is a rare nonodontogenic cyst originating in maxillofacial soft tissues. In the previous reports and literature, it is mentioned that nasolabial cyst clinical features of an asymptomatic swelling beneath the ala of nose and characteristic lip swelling are diagnostic. This is a case report of a 36-year-old male, who reported to our department with the chief complaint of swelling lateral to right ala of nose since 4 months. Characteristic lip swelling was missing. The reason for this unusual finding is not documented in the literature.